Determinant Analysis of Carpal Tunnel Syndrome and Phalen’s Test Examination of Tobacco Sorting Workers at Jember District - Paulina Samuellia; Mei Syafriadi; Hairrudin Hairrudin (Faculty of Medicine, Universitas Jember, 2024)
Tobacco sorting officers in Jember Regency are still sorting tobacco leaves manually using hand muscles which can cause Musculo Skeletal Disorders (MSDs) complaints.One of the MSDs registered at the International Labor Organization (ILO) is Carpal Tunnel Syndrome (CTS) which is a disorder resulting from compression of the median nerve in the carpal tunnel at the wrist with the main symptom being tingling, pain radiating to the fingers which can be accompanied by numbness, weakness. muscles, stiffness, and possible muscle atrophy. This study aims to determine the factors associated with CTS supported by Phalen's test. This research is expected to provide information to workers and the public regarding health problems that can be experienced by tobacco sorting workers as well as being a consideration for increasing health insurance for these workers. This research was conducted using a cross-sectional survey design at PTPN A and PT B, Jember Regency with a sample calculation using the Slovin formula and obtained 246 respondents.The data analysis technique used was univariate SPSS analysis of frequency distribution, bivariate Chi Square analysis and SEM PLS multivariate analysis. research results show that education had an effect on the symptom severity scale, age had an influence on the symptom severity scale, age had an effect on the functional status scale and age had an influence on the Phalen's test. Conclusion:Age is the dominant factor affecting the symptom severity scale, functional status scale and Phalen's test. Keywords: CTS (Carpal Tunnel Syndrome), BCTQ (Boston Carpal Tunnel Questionnaire), SSS (Symptom Severity Scale), FSS (Functional Status Scale), Phalen's Test